Outside the Fence II ‒ MSN Airport: Follow-up Study on Goose/Aircraft Strike Risk 2010 vs 2012 Before vs After Crop Habitat Modification - Whitford, Philip C. (Proceedings of the Vertebrate Pest Conference, 2014)
Five biweekly dawn-dusk observations of Canada goose movements near Dane County Madison Regional Airport (MSN) were made 10 October-15 December 2012 and results compared with similar 2010 data that had defined goose numbers, origins, and destinations for local goose flights within 10 miles of the airport across fall migration period dates. Following 2010 research suggestions, MSN airport authorities changed crop leases for lands they owned northeast of the airport to require immediate turning of corn crop residue following harvest. The affected area had been identified as a major attraction site leading to high risks of goose/aircraft strikes for Runway 21 ILS traffic in fall 2010. Following 2010 study protocol, geese were again visually tracked to observe origins/destinations for local flights and visual ground checks made to confirm locations attracting geese through airport patterns. In 2010, corn stubble fields northeast of the end of Runway resulted in observation of 696 geese entering that aircraft strike risk zone. This figure was extrapolated (total seen times 15 days for each cycle) to an estimated 10,440 risk geese entering/leaving there for the study duration. In 2012, only 31 geese were observed to fly in/out to feed there, an extrapolated value (465 geese for fall) representing a reduction of 97.1% in goose risk for that airport zone, despite average 6-fold increase in goose numbers observed at Warner Park roost area near the airport in 2012. Results indicated modification of agricultural habitat attracting geese to the airport vicinity can greatly reduce goose strike risk once attraction sites are identified. Needed changes were accomplished at no airport cost by having field leases require immediate disking of crop residue after harvest.